Social Capital Predicting the Supply Chain Skills: Mediating Role of Access to Information and Network Resources - Phatthanan Hiranrithikorn; Jutamat Sutduean (International Journal of Supply Chain Management, 2019)
Knowledge, skills and abilities are the core of success for individuals and organizations as well. The study attempted to examine the predictors of the supply chain skills. The data were collected from the employees of hospitals specifically working in the supply chain departments. Data were collected by using the self-administered questionnaire. Smart-PLS has been used for data analysis. The study results have revealed a significant positive relationship between social capital and supply chain skills. Furthermore, the study results also showed access to information and network resources as a significant mediators between the relationship of social capital and supply chain skills. It is concluded that managing the relations at work will tend to produce positive outcomes for an organization. Future directions and limitations are provided at the end of research paper.